Killer Cell Immunoglobulin-like Receptors and Their HLA Ligands are Related with the Immunopathology of Chagas Disease. - Christiane Maria Ayo; Pâmela Guimarães Reis; Márcia Machado de Oliveira Dalalio; Jeane Eliete Laguila Visentainer; Camila de Freitas Oliveira; Silvana Marques de Araújo; Divina Seila de Oliveira Marques; Ana Maria Sell (Public Library of Science (PLoS), 2015)
The aim of this study was to investigate the influence of killer cell immunoglobulin-like receptor (KIR) genes and their human leucocyte antigen (HLA) ligands in the susceptibility of chronic Chagas disease. This case-control study enrolled 131 serologically-diagnosed Chagas disease patients (59 men and 72 women, mean age of 60.4 ± 9.8 years) treated at the University Hospital of Londrina and the Chagas Disease Laboratory of the State University of Maringa. A control group was formed of 165 healthy individuals - spouses of patients or blood donors from the Regional Blood Bank in Maringa (84 men and 81 women, with a mean age of 59.0 ± 11.4 years). Genotyping of HLA and KIR was performed by PCR-SSOP. KIR2DS2-C1 in the absence of KIR2DL2 (KIR2DS2+/2DL2-/C1+) was more frequent in Chagas patients (P = 0.020; Pc = 0.040; OR = 2.14) and, in particular, those who manifested chronic chagasic cardiopathy-CCC (P = 0.0002; Pc = 0.0004; OR = 6.64; 95% CI = 2.30-18.60) when compared to the control group, and when CCC group was compared to the patients without heart involvement (P = 0.010; Pc = 0.020; OR = 3.97). The combination pair KIR2DS2+/2DL2-/KIR2DL3+/C1+ was also positively associated with chronic chagasic cardiopathy. KIR2DL2 and KIR2DS2 were related to immunopathogenesis in Chagas disease. The combination of KIR2DS2 activating receptor with C1 ligand, in the absence of KIR2DL2, may be related to a risk factor in the chronic Chagas disease and chronic chagasic cardiopathy.